Potent antibacterial activity of Terminalia chebula-based herbal soap formulation against propionibacterium acnes and its cytotoxic evaluation on human skin fibroblast cells - Almukashir, Mukhtar; Shamsi, Shamsi Saad; Alfurjany, Salahaldin; Ali, Enas; Zidan, Heba (Creative Pharma Assent, 2023)
Background: Recently, many approaches have been conducted in natural skin healthcare, with herbal remedies gaining prominence due to their perceived efficacy and fewer side effects. Herbal soaps, in particular, are noted for their antimicrobial, anti-inflammatory, and antioxidant properties, making them appealing for acne-causing bacteria such as Propionibacterium acnes, Terminalia chebula, a medicinal plant with a rich history of traditional medicinal properties, including antibacterial effects. However, limited information exists on its activity against acne-causing bacteria and its cytotoxicity on human skin cells. Methods: Our study demonstrated the anti-propionibacterium activity using a novel Terminalia chebula herbal soap formulation (TC-HSF), and to determine its cytotoxicity on Human skin fibroblast cells, Terminalia chebula aqueous extract was used to make herbal soap, the antibacterial activity was performed against wild isolated propionibacterium acne strain using well-diffusion method, MIC and time-kill Kinetics, several concentrations were evaluated for cytotoxicity on Human skin fibroblast cell lines. Results Our findings indicate a potent activity of TC-HSF against P.acne at 0.18mgwith lower CFUin tested intervals and high cell viability 98%, IC50 Value was 50mg. Conclusion: Our study highlights the promising antibacterial efficacy of TC-HSF against Propionibacterium acnes and its cytotoxic effects on human skin fibroblast cells. The research adds valuable insights into the potential of TC-HSF for acne management and underscores the importance of dosage considerations in the formulation of herbal soap products.